Study on structural behaviour of plain concrete sleeper / Adnan Derahman (Faculty of Civil Engineering, 1997)
This experimental project is a continuing study on structural behaviour of prestressed concrete sleeper (Ariffin Ngah, 1995) and (M.Yusoff Sulaiman, 1994). The experimental set-up are the same accept for this project which do the testing on a plain concrete sleeper instead of prestressed concrete sleeper. Four numbers of plain concrete sleepers were cast, one were tested under static loads and three sleepers under dynamic loads. The minimum strength of each plain concrete sleepers are 60 N/mmA2. Sleepers or ties (more specifically cross ties) have several important functions : 1 )Receive the load from the rail and distribute it over the supporting ballast at an acceptable ballast pressure level, 2)Hold the fastening system to maintain the proper track gauge, and 3)Restrain the lateral, longitudinal and vertical rail movement by anchorage of the superstructure in the ballast.